A two-stage model for social network investigations in digital forensics - David, Anne; Morris, Sarah; Appleby-Thomas, Gareth J. (Association of Digital Forensics, Security and Law, 2020)
This paper proposes a two-stage model for identifying and contextualizing features from artefacts created as a result of social networking activity. This technique can be useful in digital investigations and is based on understanding and the deconstruction of the processes that take place prior to, during and after user activity; this includes corroborating artefacts. Digital Investigations are becoming more complex due to factors such as, the volume of data to be examined; different data formats; a wide range of sources for digital evidence; the volatility of data and the limitations of some of the standard digital forensic tools. This paper highlights the need for an approach that enables digital investigators to prioritize social network artefacts to be further analysed; determine social connections in the context of an investigation e.g. a user’s social relationships, how recovered artefacts came to be, and how they can successfully be used as evidence in court
Keywords: Computer Law Commons; Information Security; Evidence Commons